Towards More Realistic Reionisation Studies and Experiments - Nasirudin, Ainulnabilah (Curtin University, 2020)
For my PhD, I aim to explore and enhance different areas of reionisation studies via simulations so that we can have a better understanding of the astrophysics of reionisation through a realistic lens. The results of my research have illuminated areas of reionisation studies that have not been properly explored before. These will be useful for current and future 21 cm experiments, especially in the era of next-generation interferometers such as the Square Kilometre Array.